Differential DNA methylation and transcriptional signatures characterize impairment of muscle stem cells in pediatric human muscle contractures after brain injury. Issue 10 (24th September 2021) - Sibley, Lydia A.; Broda, Nicole; Gross, Wendy R.; Menezes, Austin F.; Embry, Ryan B.; Swaroop, Vineeta T.; Chambers, Henry G.; Schipma, Matthew J.; Lieber, Richard L.; Domenighetti, Andrea A.
Abstract: Limb contractures are a debilitating and progressive consequence of a wide range of upper motor neuron injuries that affect skeletal muscle function. One type of perinatal brain injury causes cerebral palsy (CP), which affects a child's ability to move and is often painful. While several rehabilitation therapies are used to treat contractures, their long‐term effectiveness is marginal since such therapies do not change muscle biological properties. Therefore, new therapies based on a biological understanding of contracture development are needed. Here, we show that myoblast progenitors from contractured muscle in children with CP are hyperproliferative. This phenotype is associated with DNA hypermethylation and specific gene expression patterns that favor cell proliferation over quiescence. Treatment of CP myoblasts with 5‐azacytidine, a DNA hypomethylating agent, reduced this epigenetic imprint to TD levels, promoting exit from mitosis and molecular mechanisms of cellular quiescence. Together with previous studies demonstrating reduction in myoblast differentiation, this suggests a mechanism of contracture formation that is due to epigenetic modifications that alter the myogenic program of muscle‐generating stem cells. We suggest that normalization of DNA methylation levels could rescue myogenesis and promote regulated muscle growth in muscle contracture and thus may represent a new nonsurgical approach to treating this devastating neuromuscular condition.